Вплив лонгідази на індукований епідуральний фіброз спинного мозку - Фіщенко, Яків; Заводовський, Данило; Мотузюк, Олександр; Матвієнко, Тетяна; Ноздренко, Дмитро; Мельничук, Вікторія; Дубнік, Ольга; Fishcnenko, Yakiv; Dybnik, Olena; Zavodovskyi, Danylo; Matvienko, Tetayna; Nozdrenko, Dmytro; et al. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено вплив лонгідази в дозі 1мл/кг на індукований епідуральний фіброз спинного мозку щура. Показано зниження кількості фіброзних структур при застосуванні препарату. При цьому співвідношення кількості сполучної тканини в різні періоди після ініціації фіброзу зменшилося на 23 % після п’ятої доби експерименту й на 38 % – після 10. Зменшення максимальної товщини фіброзу становило, відповідно, 31 та 43 %. Найсуттєвіші зміни проявились у зменшенні загальної площі фіброзного утворення – на 46 % після п’ятої доби експерименту й 68 % – після 10. Результати засвідчили, що лонгідаза може знижувати епідуральну рубцеву адгезію в піддослідних щурів і чинить позитивну дію на запобігання епідуральному фіброзу й забезпечує зменшення щільності фіброзної тканини. Longidaza at dose 1ml/kg impact on artificially induced epidural fibrosis in spinal cord of the wistar rat was investigated. It was shown that administration of chosen concentration of a drug leads to fibrosis structures quantity decrease. Wherein proportion between neural and connective tissue after induction of fibrosis and drug application reduced on 23 % during 5 days and 38 % after 10 days. Maximum fibrosis thickness decline accordingly on 31 % and 43 %. The most significant changes was in decrease of the fibrosis area, up to 56 % after 5 days of the experiment and 78 after 10 days. Results show that longidaza is effectively influences measure of pathological alteration of spinal cord tissues during epidural fibrosis. Due to longidaza administration not only pathologicaly affected area is diminish but also scar tissue itself became less dense and thick. Because of the destructiveness of used fibrosis induction methods in experiment we can suggest that probably it is possible almostly prevent fibrosis using longidaza during minor traumas of spinal cord and surrounding tissues.
Longidaza Impact on Artificially Induced Spinal Cord Epidural Fibrosis in Rat
Keywords: фіброз; лонгідаза; сполучна тканина; fibrosis; longidaza; connective tissue